Determinan Konsumsi Cabai Merah Keriting pada Rumah Tangga di Baturaja Kabupaten Oku - Yetty Oktarina (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
This study aims to analyze the Determinant Consumption of Curly Red Chili in Households in Baturaja, Ogan Komering Ulu Regency. This research is a quantitative research, using primary data obtained from April to August 2018. The analysis technique uses multiple linear regression analysis, Research Results Shows when demand increases then prices also increase and vice versa. The price of substitution also affects when there is a decrease or increase in the substitution, the price of chili also experiences the same thing, while the number of families does not significantly affect the number of requests for dried chili.